The Self Determination Strategies in Spoken Language Performance Among Students of Arabic Language Education Department at Kiai Abdullah Faqih University - Muhammad A'inul Haq; Faisal Mahmoud Adam Ibrahim; Nur Hadi; Muhammad Syahrul Munir; Dibi Afriansyah (Asalibuna, 2025)
This qualitative case study investigates the implementation of Self-Determination Theory (SDT) strategies to enhance Arabic spoken language performance among students of the Arabic Language Education Department at Universitas Kiai Abdullah Faqih, a pesantren-based institution in East Java, Indonesia. The study involved five high-achieving students and three lecturers. Data were collected over a three-month period through participant observation, in-depth interviews, and document analysis (audio recordings and reflective journals), and analyzed thematically using NVivo 14. The findings reveal eight key strategies categorized according to the basic psychological needs outlined in SDT: (1) Autonomy a) integration of salafi-modern materials, b) personal goal setting, c) self-recording); (2) Competence d) daily speaking challenges, e) role-play activities); and (3) Relatedness f) language community engagement, g) classroom discussions, h) utilization of social media. The study concludes that fulfilling the needs for autonomy, competence, and relatedness through SDT-based strategies significantly improves speaking performance. Moreover, it addresses a research gap concerning the application of SDT in developing Arabic oral proficiency in pesantren-based educational settings, with implications for curriculum and pedagogy design grounded in intrinsic motivation.